2020
DOI: 10.3389/fcell.2019.00396
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin D Contributes to Anesthesia Neurotoxicity in the Developing Brain

Abstract: Anesthetic sevoflurane induces mitochondrial dysfunction, impairment of neurogenesis, and cognitive impairment in young mice, but the underlying mechanism remains to be determined. Cyclophilin D (CypD) is a modulatory factor for the mitochondrial permeability transition pore (mPTP). We, therefore, set out to evaluate the role of CypD in these sevoflurane-induced changes in vitro and in young mice. Wild-type (WT) and CypD knockout (KO) young (postnatal day 6, 7, and 8) mice received 3% sevoflurane 2 h daily and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 44 publications
(61 reference statements)
0
28
0
Order By: Relevance
“…Multiple lines of evidence support the importance of hippocampal mitochondrial homeostasis in the development of dNCR after anesthesia and surgery, although the precise mechanisms merit additional exploration [ 5 , 8 ]. We reasoned that mitochondria might play a key role in preventing cognitive impairment after anesthesia and surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple lines of evidence support the importance of hippocampal mitochondrial homeostasis in the development of dNCR after anesthesia and surgery, although the precise mechanisms merit additional exploration [ 5 , 8 ]. We reasoned that mitochondria might play a key role in preventing cognitive impairment after anesthesia and surgery.…”
Section: Resultsmentioning
confidence: 99%
“…To support normal cerebral function, the brain has a high energy demand in the form of ATP, which is supplied by mitochondria. There is significant evidence supporting the concept that maintaining mitochondrial homeostasis in neuronal cells is essential for the prevention and treatment of dNCR [ 5 , 7 , 40 ]. The objective of our current study was to identify the specific role of mitochondrial α -syn accumulation on neurotoxicity and cognition in aged mice following sevoflurane anesthesia plus surgery and also in cultured neurons exposed to LPS ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…And the others believe the increased Ca 2+ is from the membrane Ca 2+ channel, since nimodipine can block the increase of Ca 2+ and the dysfunction of mitochondria [ 33 ]. The increase of intracellular calcium flux and ROS level could stimulate the opening of mPTP, decrease MMP, and suppress ATP synthesis, subsequently leading to neuroapoptosis by the mitochondrial pathway [ 33 , 44 ].…”
Section: Apoptosis In Neural Cells By Sevoflurane Through Mitochonmentioning
confidence: 99%
“…4.1% sevoflurane was commonly used in NSCs to explore the neurotoxicity of SEV in vitro in previous studies [35,38]. There are other studies [39,40] using 3% SEV in vivo and 4.1% SEV in vitro to investigate the mechanism of SEV. The results showed that during mid-trimester, multiple exposures to sevoflurane can cause premature differentiation of NSCs in developing brains of offspring.…”
Section: Discussionmentioning
confidence: 99%